UPAYA MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI DENGAN MENGGUNAKAN METODE AKM PADA SISWA KELAS VIII SMP NEGERI 2 MAUPONGGO - Noa, Priska Ermelinda; Bela, Maria Editha; Bhoke, Wilibaldus; Tali Wangge, Maria Carmelita; Hari, Christina Lusiana (Program Studi Pendidikan Matematika, 2025)
This research aims to determine how to improve Class VIII students' literacy and numeracy skills at SMP Negeri 2 Mauponggo through the campus work program teaching Class VIII using the AKM method. This research is a qualitative descriptive study aimed at describing the literacy and numeracy skills of eighth-grade students at SMP Negeri 2 Mauponggo, Nagekeo District, East Nusa Tenggara Province. The study took place over four months, from August to early December, using various data collection techniques, including interviews, observations, tests, and documentation. The students' literacy and numeracy skills were measured using the AKM test method, which was administered twice: a pretest at the beginning of the study and a posttest at the end, involving 20 students as the research subjects. Based on the results of the pretest that the students have done, the results are quite good. With the number of class VIII students being 20 people who got a percentage result of 44% low. Meanwhile, for the Numeracy results, the percentage was 22% very low criteria, while the average student score on the literacy and numeracy post-test experienced an increase in the students' AKM results, namely the percentage of students' literacy results was 80% high criteria. while the numeracy percentage results students reached 65% currently. With this, students' abilities in AKM literacy and numeracy at SMP Negeri 2 Mauponggo have increased. Thus, it is hoped that the school will maintain and create programs to increase student literacy and numeracy.